Impact of Intensive and Semi-Intensive Farming on Histological Features and Culinary Properties of Common Carp (CYPRINUS CARPIO L.) Fillets - Eljasik Piotr; Sobczak Małgorzata; Lisiecki Sławomir; Sadowski Jacek; Panicz Remigiusz (Acta Universitatis Cibiniensis. Series E: Food Technology)
Eco-intensification of freshwater aquaculture production is considered one of the solutions to achieve global food security. However, intensification of the production may come with product quality trade-offs, which are unlikely to be accepted by modern consumers. The aim of this study was to evaluate impact of intensive cage farming and typical semi-intensive pond culture on culinary and histological characteristics of common carp (Cyprinus carpio L.) fillets. In intensive cage culture common carp were fed formulated feed for 60 days, while in semi-intensive pond farming fish utilised natural food and supplementary grains (triticale) for 90 days to achieve similar weight. Next, fish were sacrificed, filleted and quality of fillets, i.e. pH, colour, histology of muscle tissue, texture and sensory properties were assessed. The results showed that intensive cage culture, because of constant water flow, contributed to muscle development through hypertrophy mechanism and resulted with higher number of large muscle fibers (over 60 μm in diameter) compared to semi-intensive pond farming. The differences in histology of muscle tissue were correlated with sensory characteristics of fillets, but not with texture instrumental analysis. Appearance (colour) and taste of the fillets of common carp from semi-intensive pond farming was more attractive from consumers’ perspective, especially that no negative features, such as off-flavour were noted compared to intensive cage culture.